2019
DOI: 10.22319/rmcp.v10i1.4631
|View full text |Cite
|
Sign up to set email alerts
|

Rendimiento de forraje y sus componentes en variedades de alfalfa en el altiplano de México

Abstract: La leguminosa más utilizada para el ganado lechero en México es la alfalfa (Medicago sativa L.), debido a su alto rendimiento y calidad nutrimental. El objetivo de éste estudio fue evaluar la respuesta productiva y componentes del rendimiento de cinco variedades de alfalfa con intervalos de corte definidos estacionalmente. Las variedades Aragón, Valenciana, Chipilo, Milenia y Oaxaca se distribuyeron aleatoriamente en 20 parcelas experimentales de 12 x 9 m, de acuerdo a un diseño de bloques completos al azar co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…The opposite occurred in the stem component, with higher yields after a cutting frequency of 64 days, with an average of 73 % stem in the three planting densities (p < 0.05). In turn, Rojas- García et al (2017) reported alfalfa (Medicago sativa L.) yield and obtained an average of 45 % leaves at the 29-day cutting frequency, which is comparable to the values obtained in this study. Regarding the height of the chepil grassland at different sowing densities and cutting stages (Figure 1), at the 43 to the 79-day cutting frequencies, the plants presented greater height (163 to 203 cm) independently of the sowing density (p < 0.05); however, at a density of 200 000 plants ha -1 , it was observed that the greatest average height was 163 cm, while at a sowing density of 50 000 plants ha -1 , the lowest was 154 cm (p < 0.05).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The opposite occurred in the stem component, with higher yields after a cutting frequency of 64 days, with an average of 73 % stem in the three planting densities (p < 0.05). In turn, Rojas- García et al (2017) reported alfalfa (Medicago sativa L.) yield and obtained an average of 45 % leaves at the 29-day cutting frequency, which is comparable to the values obtained in this study. Regarding the height of the chepil grassland at different sowing densities and cutting stages (Figure 1), at the 43 to the 79-day cutting frequencies, the plants presented greater height (163 to 203 cm) independently of the sowing density (p < 0.05); however, at a density of 200 000 plants ha -1 , it was observed that the greatest average height was 163 cm, while at a sowing density of 50 000 plants ha -1 , the lowest was 154 cm (p < 0.05).…”
Section: Resultssupporting
confidence: 88%
“…This behavior is possibly due to the loss of lower leaves from the plant canopy, plant maturity, and competition with other plants (Maldonado-Peralta et al, 2019). Several researchers report an optimum intercepted radiation of 95 %, indicating that this is when the best structural characteristics of legume grassland are found (Rojas- García et al, 2017). On the other hand, Alonzo-Griffith and Paniagua-Alcaraz ( 2010) report similar values of legume intercepted radiation, with an average of 90 %.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Por otro lado, Lamb et al (2014) observaron una relación de hoja/tallo mayor en los meses de junio (2.0) y julio (2.5) a edades tempranas de rebrote y disminuyó a etapas tardías de floración (> 1.0), dadas las condiciones ambientales cálido-secas y cielos mayormente despejados en verano, en contraste con inviernos fríos. En otras investigaciones se reportan valores de RHT de 1.49 en otoño e invierno y menores en verano y primavera, de 0.92 y 0.94, respectivamente (Rojas-García et al, 2017). Zaragoza et al (2009) observaron una disminución de la RHT a mayor edad de rebrote, cuando se registró mayor acumulación de materia seca a los 35 DDR, en verano, otoño y primavera, con valores de 0.8, 0.7 y 0.6, respectivamente; sin embargo, en invierno fue de 0.8 a los 42 DDR.…”
Section: Ddrunclassified
“…However, the forage yield of grasses largely depends on factors such as the genotype and agronomic management (Gándara et al, 2017). The agronomic management includes the intensity and frequency of defoliation, which are factors that modify the forage yield (Hernández et al, 2012;Rojas-García et al, 2018). When Cruz et al (2017) evaluated Chetumal grass (Brachiaria humidicola) at different intervals (21 and 28 days) and grazing intensities (severe: 9-11 and light: 13-15 cm), they obtained greater forage accumulation when light grazing took place every 28 days (9,771 kg DM ha 1 ) than with severe grazing (8,337 kg DM ha 1 ).…”
Section: Introductionmentioning
confidence: 99%